A look at the problem of exposure of the population caused by X-ray diagnostics: approaches to analysis and forecasting - Sevalnev, A. I.; Kutsak, A. V.; Sharavara, L. P.; Volkova, Yu. V.; Севальнєв, Анатолій Іванович; Куцак, Алла Валеріївна; Шаравара, Лариса Павлівна; Волкова, Юлія Володимирівна (My University, 2021)
The article is devoted to the analysis of limitation of dose load on the population as a result of radiological researches. It is especially actual and represents rather high scientific and practical interest. In this regard, it is very important to have information about the state of the dose load of the population in separate regions and to rank types of diagnostics by the amount of their contribution to the total dose of medical exposure. The aim of the work was to study the state of dose load of the population of Zaporizhzhia region due to X-ray diagnostics, to develop approaches to analysis and forecasting regarding its limitation. Analytical, statistical calculation and logical generalization methods were used in the course of the work. We used the results of studies carried out in accordance with the regional “Program for the Protection of the Population of Zaporizhzhia Region from the Effect of Ionizing Radiation. The authors analyzed scientific publications (15 sources), including 9 Ukrainian and 6 foreign on the relevance of the problem of exposure of the population caused by X-ray diagnostics. The analysis of the results allowed to determine that in 2010-2014 the radiation dose of the population of Zaporizhzhia region due to X-ray diagnostics averaged 0.92 mSv year-1, in 2015-2016 the dose increased and amounted to 0.96 mSv year-1. The proposed approach to the analysis makes it possible to summarize and model data on radiological studies of the population over a long period of time, to identify persistent trends in the contribution of different types of radiation diagnostics to the dose of medical radiation. All this is necessary for the development, first of all, of measures to reduce the frequency of radiography, its replacement by other diagnostic methods. Priority tasks aimed at reducing the dose load of the population due to X-ray examinations are proposed. Стаття присвячена питанням обмеження дозового навантаження населення за рахунок рентгенологічних досліджень, відзначається особливою актуальністю і становить достатньо високий як науковий, так і практичний інтерес. У зв’язку з цим дуже важливо мати інформацію про стан дозового навантаження населення в окремих регіонах і ранжування видів діагностики за величиною внеску їх у загальну дозу медичного опромінення. Метою роботи було вивчити стан дозового навантаження населення Запорізької області за рахунок рентгенодіагностики, розробити підходи до аналізу та прогнозування щодо його обмеження. При проведенні роботи використовувались методи дослідження: аналітичний, статистичний, розрахунковий та логічного узагальнення. Були використані результати досліджень, проведені згідно з регіональною «Програмою захисту населення Запорізької області від впливу іонізуючого випромінювання». Автори провели аналіз наукових публікацій (15 джерел), з них 9 вітчизняних і 6 зарубіжних, щодо актуальності проблеми опромінення населення за рахунок рентгенодіагностики. Аналіз результатів дозволив визначити, що в 2010-2014 рр. доза опромінення населення Запорізької області за рахунок рентгенодіагностики в середньому становила 0,92 мЗв рік-1, у 2015-2016 рр. доза збільшилась і становила 0,96 мЗв рік-1. Запропонований підхід до аналізу дає можливість узагальнити й моделювати дані про рентгенологічні дослідження населення за тривалий період часу, виявити стійкі тенденції внеску різних видів променевої діагностики в дозу медичного опромінення. Усе це необхідно для опрацювання, у першу чергу, заходів щодо зменшення частоти призначення рентгенографії, заміни її іншими методами діагностики. Запропоновано пріоритетні завдання, спрямовані на зменшення дозового навантаження населення за допомогою рентгенологічних досліджень.
Погляд на проблему опромінення населення за рахунок рентгенодіагностики: підходи до аналізу та прогнозування
Keywords: medical exposure of the population; X-ray diagnostics researches; the state of the dose load of the population; медичне опромінення; рентгенодіагностичні дослідження; стан дозового навантаження населення; медицинское облучение; рентгенодиагностические исследования; дозовой нагрузки населения